Sexuality and law in the Torah - Lipka, Hilary B.; Wells, Bruce (Scriptural traces: critical perspectives on the reception and influence of the Bible, 2020)
"An examination of the laws in the Hebrew Bible governing sexual relations and of the often implicit motivations behind these laws. It also considers narrative and poetic texts where legal traditions and ideas concerning sexual status and behavior intersect and provide important insight into ancient Israel's social norms and expectations. The book contains extended treatments on the nature and function of marriage and divorce in ancient Israel, the role of sexual regulations in maintaining what biblical authors believed was proper social order, and the different types of sexualities that may have existed in ancient Israel"--